Examining the association between exposome score for schizophrenia and cognition in schizophrenia, siblings, and healthy controls: Results from the EUGEI study. (May 2023) - Fusar-Poli, Laura; Prachason, Thanavadee; Erzin, Gamze; Pries, Lotta-Katrin; Brondino, Natascia; Politi, Pierluigi; Delespaul, Philippe; Kenis, Gunter; Luykx, Jurjen J; Lin, Bochao D; Richards, Alexander L; Akdede, Berna; et al.
Highlights: Exposome score for Schizophrenia (ES-SCZ) is a weighted sum score of environmental factors associated with schizophrenia. ES-SCZ was not associated with neurocognition, social cognition, or perception in people with SSD. ES-SCZ was negatively associated with neurocognition but positively with social cognition in non-psychotic participants. Longitudinal studies may clarify the effect of environment on cognitive functioning in SSD. Abstract: Background: People with schizophrenia spectrum disorders (SSD) frequently present cognitive impairments. Here, we investigated whether the exposome score for schizophrenia (ES-SCZ) - a cumulative environmental exposure score - was associated with impairments of neurocognition, social cognition, and perception in patients with SSD, their unaffected siblings, and healthy controls. Methods: This cross-sectional sample consisted of 1200 patients, 1371 siblings, and 1564 healthy controls. Neurocognition, social cognition, and perception were assesed using a short version of the Wechsler Adult Intelligence Scale–Third Edition (WAIS-III), the Degraded Facial Affect Recognition Task (DFAR), and the Benton Facial Recognition Test (BFR), respectively. Regression models were used to analyze the association between ES-SCZ and cognitive domains in each group. Results: There were no statistically significant associations between ES-SCZ and cognitive domains in SSD. ES-SCZ was negatively associated with T-score of cognition in siblings (B=-0.40, 95% CI -0.76 to -0.03) and healthy controls (B=-0.63, 95% CI -1.06 to -0.21). Additionally, ES-SCZ was positively associated with DFAR-total in siblings (B=0.83, 95% CI 0.26 to 1.40). Sensitivity analyses excluding cannabis use history from ES-SCZ largely confirmed the main findings. Conclusions: Longitudinal cohorts may elucidate how environmental exposures influence the onset and course of cognitive impairments in trans-syndromic psychosis spectrum.